Economy of power resources by means of improving the normative base of production of cellular concrete - Serdiuk, V. R.; Avhustovych, B. I. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The article deals with the problem of energy saving in the building sector in the context of improving the regulatory framework for the production of cellular concrete as the structurally-efficient thermal insulation wall material.